EFFECT OF DIPPING IN GIBBERLLIC ACID AND SPRAYING NUTRIENT SOLUTION AGRO LEAF ON SOME VEGETATIVE GROWTH AND YIELD OF JERUSALUM ARTICHOKE. - & et al., Sadik (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This study was conducted in experimental fields, Department of Horticulture, University of Bagdad, in Abu-Graib  during season 2011-2012 for jerusalum artichoke. This study was included the effect of dipping tubers in three concentrations of GA3(2.5,5,10g/l) (G1,G2,G3),as well as to control treatment (G0), and spraying nutrient solution Agro leaf A1 (8g/l), as well as to control treatment (A0). This study was made by using Factorial experiment (4*2) within the design RCBD with three replicates. Results could be summarized as follows: G3A0 increased field emergence (12.00 day), G2A0 increased percentage of germination (99.33%) and G2A1 increased number of branches (4.60 stem.plant-1) but the treatment G1A1gave highest rate for number of leaves, leaf area, guide of leaf area, dry weight of the vegetative parts and dry weight of 100gm tubers as(4495.10 leaf.plant-1, 2246.20 dsm2, 99.84, 922.40g, 24.00g.) respectively. The treatments gave significant differences quantity yield, so treatment G3A0 gave highest weight of the tubers as(45.55g.) but the treatment G3A1 gave highest number of the tubers as(68.00 tuber.plant-1 ) and highest yield of plant as (2890g/plant).